Breaking through : how female athletes shattered stereotypes in the Roaring Twenties - Macy, Sue (National Geographic, 2020)
Offers illustrated profiles of female athletes in the 1920s who broke barriers and defied sexism and misogyny to redefine femininity in America. Also looks at how the cultural mores of the time helped set the stage for women to break through in sports, and how this revolution changed not just athletics, but the broader social scope of America.